Research-based learning in teaching the Russian language at university: theory, methodology and pedagogical conditions for implementation - Rakhmonov, Azizkhon Bositkhonovich (The Lingua Spectrum, 2026)
The article is devoted to the theoretical and methodological substantiation of research activities of students in Russian language classes in higher education. The paper reveals the essence of research activity as a pedagogical category, its place in modern educational concepts, and the specifics of its organization in language education. Domestic and international approaches to defining research competence are analyzed; theoretical foundations – the activity approach, constructivism, and self-determination theory – are examined in relation to Russian language teaching. Pedagogical conditions are identified under which research activity becomes an effective instrument for forming linguistic, communicative, and metacognitive competencies. Special attention is paid to the methodological apparatus: diagnostics, assessment, and evaluation of students' research skills; the use of analytical rubrics and performance-based assessment; and the development of transferable skills and soft skills. The results of the analysis of international studies in the field of inquiry-based learning and problem-based learning are presented. The conclusion is drawn that systematic incorporation of research tasks into the Russian language learning process promotes the development of critical thinking, student autonomy, and improvement of the quality of language education.